Molecularly imprinted polymer, preparation method thereof and application of molecularly imprinted polymer in extraction of thiophene in coking crude benzene
By preparing high adsorption amount and easy-to-separate molecular imprinted polymers, the problems of low adsorption amount and high cost in the removal and recovery of thiophene in coked crude benzene are solved, and efficient recovery of thiophene and improved benzene product quality are achieved.
Patent Information
- Application Number
- CN202411558534.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing surface molecular imprinting adsorption and desulfurization technology has problems such as low adsorption, high cost and difficult separation in the removal and recovery of thiophene in coked crude benzene, which limits its application prospects.
Using a preparation method of molecularly imprinted polymer, mesoporous carbon coated nanoferrous tetraoxide is obtained by mixing iron salt with asphalt, followed by silanization, and reacting with thiophene and functional monomer in an organic solvent. A crosslinking agent is added to react with an initiator to form a molecularly imprinted polymer with high adsorption amount and easy separation.
The adsorption capacity and adsorption rate are improved, the efficient recovery of thiophene is achieved, the sulfur content in coked benzene is reduced, the quality of benzene products is improved, and the economic benefits of thiophene products are increased.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal chemical industry, and in particular relates to a molecular imprinting polymer and a preparation method thereof and application thereof in extracting thiophene from coking crude benzene. Background Art
[0002] The thiophene content in domestic coking crude benzene is generally high. If it is not removed, it will seriously affect the subsequent deep processing. Thiophene is an impurity that must be removed during the refining process of crude benzene. However, in fact, thiophene has high application value and economic value, and is often used as a synthetic pharmaceutical intermediate, pesticide intermediate and photosensitive material. Therefore, recycling thiophene in coking crude benzene can not only improve the quality of coking benzene but also increase the economic benefits of thiophene products.
[0003] Since benzene and thiophene have similar molecular structures and chemical properties, they are not easy to remove. Surface molecular imprinting adsorption desulfurization technology has the advantages of high selectivity, mild adsorption conditions, simple operation and low cost. For example, Chinese patent publication number CN101229507B discloses molecular imprinting adsorption resins for benzothiophene compounds and their preparation methods and applications, Chinese patent publication number CN102731719A discloses a "molecular imprinting material for desulfurization and its manufacturing method" and Chinese patent publication number CN112794963A discloses a "molecular imprinting polymer for removing thiophene sulfur from gasoline and its preparation method" to prepare a molecular imprinting adsorbent for adsorbing thiophene compounds. The adsorbent has high selectivity and is very effective for thiophene compounds. The recovery rate is high; Chinese patent publication number CN109589808A discloses a method for preparing a carbon-based surface molecularly imprinted two-dimensional composite membrane. The composite membrane is different from traditional powder adsorbents and solves the problem that traditional powder adsorbents are difficult to separate and recover, but the preparation process is complicated and the cost is increased; Chinese patent publication number CN102675537B discloses a method for preparing a magnetic material for removing dibenzothiophene from oil products. A magnetic molecularly imprinted adsorbent containing nano-ferroferric oxide is prepared, which can be quickly separated and recovered under the action of an external magnetic field.
[0004] However, at present, the surface molecular imprinting adsorption desulfurization technology disclosed in the above patents is all applied to the field of fuel oil desulfurization. The main reason is that the adsorption capacity of the current surface molecular imprinting adsorbent is generally low, which is suitable for fuel oil with low sulfur content. However, the thiophene content of coking crude benzene is high, and an adsorbent with high adsorption capacity is required, which limits the application of surface molecular imprinting adsorbent in removing and recovering thiophene from coking crude benzene. In view of the many advantages of surface molecular imprinting adsorption desulfurization technology, it is of great application prospect to develop a surface molecular imprinting adsorbent with high adsorption capacity, easy separation and low cost to extract thiophene from coking crude benzene. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a molecular imprinting polymer with high adsorption capacity that is simple to prepare, low in cost and easy to separate, and a preparation method thereof, and an application thereof in extracting thiophene from coking crude benzene.
[0006] The present invention provides a method for preparing a molecularly imprinted polymer, comprising the following steps:
[0007] S1) mixing iron salt with asphalt, and calcining in a protective atmosphere to obtain mesoporous carbon-coated nano-iron tetroxide;
[0008] S2) subjecting the mesoporous carbon-coated ferrosoferric oxide to silanization treatment to obtain silanized mesoporous carbon-coated ferrosoferric oxide;
[0009] S3) mixing the silanized mesoporous carbon-coated ferrosoferric oxide, thiophene and functional monomers in an organic solvent, then adding a crosslinking agent and an initiator and heating in a protective atmosphere for reaction to obtain a molecular imprinting polymer.
[0010] Preferably, the mass ratio of the iron salt to asphalt is (1-3):1.
[0011] Preferably, the calcination temperature in step S1) is 500°C to 600°C; the calcination heating rate is 5 to 15°C / min; and the calcination time is 0.5 to 3 hours.
[0012] Preferably, the step S2) is specifically:
[0013] The mesoporous carbon-coated ferrosoferric oxide and a silane coupling agent are mixed in an alcohol solution, and heated to react in a protective atmosphere to obtain silanized mesoporous carbon-coated ferrosoferric oxide.
[0014] Preferably, the ratio of the mesoporous carbon-coated ferrosoferric oxide to the silane coupling agent is (0.5-1) g: (2.5-5) mL.
[0015] Preferably, the alcohol solution is a mixed solution of an alcohol solvent and water; the volume ratio of the alcohol solvent to water is (3-6): (1-2);
[0016] The ratio of the mesoporous carbon-coated ferroferric oxide to the alcohol solution is (0.5-1) g: (40-80) mL;
[0017] The mixing time is 10 to 60 minutes; the heating reaction temperature is 60° C. to 70° C.; and the heating reaction time is 3 to 5 hours.
[0018] Preferably, the ratio of the silanized mesoporous carbon-coated ferrosoferric oxide, thiophene and functional monomer is 0.5 g: (2-5) mmol: (8-20) mmol;
[0019] The ratio of the silanized mesoporous carbon-coated ferrosoferric oxide, the crosslinking agent and the initiator is 0.5 g: (8-20) mmol: (0.04-0.1) g.
[0020] Preferably, the mixing time in step S3) is 10 to 100 minutes;
[0021] The reaction temperature is 50°C to 70°C; the reaction time is 15 to 30 hours.
[0022] The invention also provides a molecular imprinting polymer prepared by the preparation method.
[0023] The present invention also provides an application of the molecular imprinting polymer prepared by the preparation method in extracting thiophene from coking crude benzene.
[0024] The invention provides a method for preparing a molecular imprinting polymer, comprising the following steps: S1) mixing iron salt and asphalt, and calcining them in a protective atmosphere to obtain mesoporous carbon-coated nano-iron tetroxide; S2) subjecting the mesoporous carbon-coated iron tetroxide to silanization treatment to obtain silanized mesoporous carbon-coated iron tetroxide; S3) mixing the silanized mesoporous carbon-coated iron tetroxide, thiophene and a functional monomer in an organic solvent, and then adding a crosslinking agent and an initiator, heating and reacting in a protective atmosphere to obtain a molecular imprinting polymer. Compared with the prior art, the mesoporous carbon-coated nano-ferroferric oxide prepared by the present invention has a large specific surface area, rich pore volume and good dispersibility. The thiophene imprinted material synthesized as a matrix material greatly improves the adsorption capacity and adsorption rate compared with the traditional molecular imprinted material, and because it is coated with magnetic nano-ferroferric oxide, it can be quickly separated under an external magnetic field, the adsorbent is easy to recycle and reuse, and the service life of the adsorbent is extended; in addition, the synthesized thiophene imprinted material can be applied to coking crude benzene with a high thiophene content, which not only reduces the sulfur content in the crude benzene, improves the quality of the benzene product, but also increases the profit of the thiophene product. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The invention provides a method for preparing a molecular imprinting polymer, comprising the following steps: S1) mixing iron salt and asphalt, and calcining them in a protective atmosphere to obtain mesoporous carbon-coated nano-iron tetroxide; S2) subjecting the mesoporous carbon-coated iron tetroxide to silanization treatment to obtain silanized mesoporous carbon-coated iron tetroxide; S3) mixing the silanized mesoporous carbon-coated iron tetroxide, thiophene and a functional monomer in an organic solvent, and then adding a crosslinking agent and an initiator, heating and reacting in a protective atmosphere to obtain a molecular imprinting polymer.
[0027] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0028] The iron salt is mixed with asphalt, and calcined in a protective atmosphere to obtain mesoporous carbon-coated nano-ferrosoferric oxide; the iron salt can be any iron salt known to those skilled in the art, without any special restrictions, and preferably ferric sulfate and / or ferrous sulfate in the present invention; the asphalt can be any asphalt known to those skilled in the art, without any special restrictions, and preferably coal asphalt in the present invention, and more preferably high-temperature coal asphalt; the softening point of the asphalt is preferably 100°C to 110°C, more preferably 102°C to 108°C, more preferably 102°C to 105°C, and most preferably 103°C to 104°C; the iron salt The mass ratio of the asphalt to the asphalt is preferably (1-3):1, more preferably (1.5-2.5):1, and more preferably 2:1; the mixing method can be a method well known to those skilled in the art, and there is no special limitation. In the present invention, grinding mixing is preferred; the mixing time is preferably 10-60 min, more preferably 20-50 min, more preferably 20-40 min, and most preferably 30 min; the protective atmosphere can be a protective atmosphere well known to those skilled in the art, and there is no special limitation. In the present invention, nitrogen is preferred; the calcination temperature, that is, the insulation temperature is preferably The temperature is preferably 500°C to 600°C, more preferably 550°C to 600°C, more preferably 580°C to 600°C, and most preferably 600°C; the heating rate of calcination is preferably 5 to 15°C / min, more preferably 8 to 12°C / min, and more preferably 10°C / min; the calcination time, i.e., the holding time, is preferably 0.5 to 3h, more preferably 1 to 3h, more preferably 1.5 to 2.5h, and most preferably 2h; during the calcination process, a sodium hydroxide solution may be used to absorb the generated sulfur dioxide; after the calcination is completed, it is preferably cooled to room temperature in a protective atmosphere and washed with an alcohol aqueous solution After washing and drying, mesoporous carbon-coated nano-iron tetroxide is obtained; the volume ratio of the alcohol solvent to water in the alcohol aqueous solution is preferably 1: (1-3), more preferably 1: (1.5-2.5), and more preferably 1: 2; the alcohol solvent can be an alcohol solvent well known to those skilled in the art, and there is no special restriction. In the present invention, ethanol is preferably used; the water is preferably deionized water; the number of washings is preferably 2-4 times, and more preferably 3 times; the drying is preferably vacuum drying; the drying temperature is preferably 70°C-90°C, more preferably 75°C-85°C, and more preferably 80°C.
[0029] The mesoporous carbon-coated ferroferric oxide is subjected to silanization treatment to obtain silanized mesoporous carbon-coated ferroferric oxide; the silanization treatment method can be a method well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably carried out in the following manner: the mesoporous carbon-coated ferroferric oxide is mixed with a silane coupling agent in an alcohol solution, and heated to react in a protective atmosphere to obtain silanized mesoporous carbon-coated ferroferric oxide; the silane coupling agent can be a silane coupling agent well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably γ-isocyanate propyl triethoxy silane, acrylate propyl trimethoxy silane, γ-aminopropyl triethoxy silane, N-β-(aminoethyl) -γ-aminopropyltrimethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, γ-glycidyloxypropyltrimethoxysilane (KH560), γ-methacryloxypropyltrimethoxysilane (KH570) and γ-mercaptopropyltrimethoxysilane (KH580) One or more; the ratio of the mesoporous carbon-coated ferrosoferric oxide to the silane coupling agent is preferably (0.5-1) g: (2.5-5) mL, more preferably (0.5-1) g: (2.5-4) mL, and more preferably (0.5-0.8) g: (2.5-4) mL; In some embodiments provided by the present invention, the ratio of the mesoporous carbon-coated ferrosoferric oxide to the silane coupling agent is preferably (0.5-1) g: (2.5-4) mL, more preferably (0.5-0.8) g: (2.5-4) mL. The specific ratio is 0.5g:2.5mL or 0.8g:4mL; the alcohol solution is preferably a mixed solution of an alcohol solvent and water; the volume ratio of the alcohol solvent to water is preferably (3-6):(1-2), more preferably (3-5):(1-2), more preferably (3-5):(1-1.6), and most preferably (3-4.8):(1-1.6); the alcohol solvent is an alcohol solvent well known to those skilled in the art, and there is no special restriction. In the present invention, ethanol is preferably used; the ratio of the mesoporous carbon-coated ferroferric oxide to the alcohol solution is preferably (0.5-1)g:(40-80)mL, more preferably (0.5-1)g:(40-70)mL, and more preferably (0.5-1)g:(40-70)mL. The mixture is preferably (0.5-1) g: (40-60) mL, and most preferably (0.5-0.8) g: (40-60) mL; the mixing method is any method known to those skilled in the art, and is not particularly limited. In the present invention, ultrasonic dispersion is preferred; the mixing time is preferably 10-60 min, and is more preferably 20-50 min, and is more preferably 30-40 min; the protective atmosphere is any protective atmosphere known to those skilled in the art, and is not particularly limited. In the present invention, nitrogen is preferred; the temperature of the heating reaction is preferably 60-70 ° C, and is more preferably 65 ° C; the heating reaction time is preferably 3-5 h, and is more preferably 3.5-4.5h, preferably 4h; the heating reaction is preferably carried out under stirring; after the heating reaction is completed, it is preferably cooled, and after the solid is separated, it is washed with ethanol and dried to obtain silanized mesoporous carbon coated with ferrosoferric oxide; the drying temperature is preferably 50℃~70℃, more preferably 55℃~65℃, and more preferably 60℃. .
[0030] The silanized mesoporous carbon-coated ferrosoferric oxide, thiophene and functional monomer are mixed in an organic solvent; the functional monomer is a functional monomer well known to those skilled in the art, and is not particularly limited. In the present invention, methyl acrylate is preferred; the ratio of the silanized mesoporous carbon-coated ferrosoferric oxide, thiophene and functional monomer is preferably 0.5 g: (2-5) mmol: (8-20) mmol, more preferably 0.5 g: (2-5) mmol: (10-20) mmol, further preferably 0.5 g: (3-5) mmol: (10-20) mmol, and most preferably 0.5 g: (3-5) mmol: (12-20) mmol; the organic solvent is an organic solvent well known to those skilled in the art, and is not particularly limited. In the present invention, acetonitrile and / or N,N-dimethylformamide are preferred; the ratio of the silanized mesoporous carbon-coated ferrosoferric oxide to the organic solvent is preferably (0.5-1) g: 100 mL, and more preferably (0 .5~0.8)g:100mL; the mixing method is a method well known to those skilled in the art and is not particularly limited. In the present invention, ultrasound and / or stirring are preferred, and ultrasound first and then stirring are more preferred; the mixing time is preferably 10~100min, more preferably 30~100min, more preferably 60~100min, and most preferably 90~100min; in the present invention, it is preferred to first ultrasonically disperse the silanized mesoporous carbon-coated ferrosoferric oxide in an organic solvent, and then add thiophene and functional monomers and continue to ultrasonicate and then stir; the ultrasonic dispersion time is preferably 5~15min, more preferably 8~2min, and more preferably 10min; the continued ultrasonic time is preferably 10~30min, more preferably 15~25min, and more preferably 20min; the stirring time is preferably 30~60min, more preferably 40~60min, more preferably 50~60min, and most preferably 60min.
[0031] Then, a crosslinking agent and an initiator are added and heated in a protective atmosphere for reaction; the crosslinking agent can be a crosslinking agent well known to those skilled in the art, and there is no special limitation, and in the present invention, ethylene glycol dimethacrylate is preferred; the initiator can be an initiator well known to those skilled in the art, and there is no special limitation, and in the present invention, an azo initiator is preferred; the azo initiator is preferably azobisisobutyronitrile and / or azobisisoheptanenitrile; the ratio of the silanized mesoporous carbon-coated ferrosoferric oxide, the crosslinking agent and the initiator is preferably 0.5 g: (8-20) mmol: (0.04-0.1) g, and more preferably 0.5 g: (10-20) mmol: (0.04-0.1) g, more preferably 0.5g:(10-20)mmol:(0.05-0.1)g, most preferably 0.5g:(12-20)mmol:(0.06-0.1)g; in some embodiments provided by the present invention, the ratio of the silanized mesoporous carbon-coated ferrosoferric oxide, the cross-linking agent and the initiator is specifically 0.5g:12mmol:0.06g or 0.5g:20mmol:0.1g; the reaction temperature is preferably 50℃~70℃, more preferably 55℃~65℃, and more preferably 60℃; the reaction time is preferably 15-30h, more preferably 18-30h, more preferably 20-30h, and most preferably 24h.
[0032] After the reaction is completed, the solid is preferably separated, washed, and dried to obtain a molecular imprinted polymer; the separation of the solid is preferably carried out using a magnet; the washing is preferably carried out using an alcohol solvent and a mixed solution of an alcohol solvent and an organic acid in sequence; the alcohol solvent is an alcohol solvent well known to those skilled in the art, and is not particularly limited. In the present invention, ethanol and / or methanol are preferably used; the alcohol solvent in the mixed solution of an alcohol solvent and an organic acid is preferably methanol; the organic acid in the mixed solution of an alcohol solvent and an organic acid is preferably acetic acid; the volume ratio of the alcohol solvent to the organic acid in the mixed solution of an alcohol solvent and an organic acid is preferably (8 to 10):1, more preferably (8.5 to 9.5):1, and more preferably 9:1; the washing is preferably carried out until no sulfur content is detected in the solution; the drying temperature is preferably 50°C to 70°C, more preferably 55°C to 65°C, and more preferably 60°C.
[0033] The mesoporous carbon-coated nano-iron tetroxide prepared by the present invention has a large specific surface area, rich pore volume and good dispersibility. The thiophene imprinted material synthesized as a matrix material greatly improves the adsorption capacity and adsorption rate compared with the traditional molecular imprinted material, and because it is coated with magnetic nano-iron tetroxide, it can be quickly separated under an external magnetic field, the adsorbent is easy to recycle and reuse, and the service life of the adsorbent is extended; in addition, the synthesized thiophene imprinted material can be applied to coking crude benzene with a high thiophene content, which not only reduces the sulfur content in the crude benzene, improves the quality of the benzene product, but also increases the profit of the thiophene product.
[0034] The present invention also provides a molecular imprinted polymer prepared by the above preparation method; the adsorption capacity of the molecular imprinted polymer for thiophene is preferably 30-50 mg / g, more preferably 33-45 mg / g, and even more preferably 33-43.6 mg / g.
[0035] The present invention also provides an application of the molecular imprinting polymer prepared by the above preparation method in extracting thiophene from coking crude benzene; the mass ratio of the molecular imprinting polymer to the coking crude benzene is preferably 1: (5-20), more preferably 1: (5-15), further preferably 1: (8-12), and most preferably 1: 10.
[0036] The molecular imprinted polymer prepared by the present invention has the characteristics of high selectivity, high adsorption capacity, fast adsorption rate and easy separation, and has good effect in extracting and recovering thiophene from crude benzene in coking. The coking plant uses molecular imprinted polymer to recover thiophene from crude benzene, which not only increases the product revenue of thiophene, but also effectively reduces the cost of crude benzene refining. Moreover, the molecular imprinted polymer can be recycled after separation, and has low application cost. It has strong feasibility of promoting and applying it inside and outside the company, and has broad prospects.
[0037] In order to further illustrate the present invention, a molecular imprinting polymer provided by the present invention, a preparation method thereof and an application thereof in extracting thiophene from coking crude benzene are described in detail below in conjunction with examples.
[0038] The reagents used in the following examples are all commercially available; the softening point of the high-temperature coal tar pitch used in the examples is about 103°C.
[0039] Example 1
[0040] (1) Preparation of mesoporous carbon-coated nano-iron tetroxide matrix: Weigh 10g FeSO4·7H2O and 5g high-temperature coal tar pitch, mix them, and place the resulting mixture in a ball mill for 30 minutes to grind it into a uniform powder. Then place the mixture powder in a tube furnace and heat it from ambient temperature to 600°C under nitrogen protection, with a heating rate of 10°C / min and a calcination time of 2 hours. Finally, the calcined product was cooled to ambient temperature under nitrogen protection, washed three times with a mixed solution of ethanol and water (ethanol and deionized water volume ratio 1:2), and then dried in a vacuum drying oven at 80°C to constant weight to obtain mesoporous carbon-coated nano-iron tetroxide. Sodium hydroxide solution was used to absorb the sulfur dioxide produced during the reaction.
[0041] (2) Surface silanization of mesoporous carbon-coated nano-iron tetroxide matrix: Weigh 0.5g of mesoporous carbon-coated nano-iron tetroxide, then add 10mL of deionized water, 30mL of ethanol and 2.5mL of KH570, and ultrasonically disperse for 30min. After ultrasonication, under nitrogen protection, magnetic stirring, react in a water bath at 65℃ for 4h. After the reaction, wait for the solution to cool, separate the product with a magnet, and then wash it thoroughly with ethanol. The washed product is dried in an oven at 60℃ to obtain silanized mesoporous carbon-coated nano-iron tetroxide.
[0042] (3) Preparation of thiophene molecular imprinting polymer: Weigh 0.5g of silanized mesoporous carbon-coated nano-iron tetroxide and disperse it in 100mL of acetonitrile. Ultrasonicate for 10min to make it evenly dispersed. Then add 3mmol of thiophene and 12mmol of methacrylic acid. Continue ultrasonication for 20min and then magnetically stir at room temperature for 1 hour. Then add 12mmol of ethylene glycol dimethacrylate and 0.06g of azobisisobutyronitrile, magnetically stir, heat to 60℃ under nitrogen protection, and react for 24h. After the reaction is completed, separate the product with a magnet, wash it three times with ethanol, and then repeatedly elute it with a mixed solution of methanol and acetic acid in a volume ratio of 9:1 until no sulfur content is detected in the eluent. Finally, dry the obtained product in an oven at 60℃ to obtain a thiophene molecular imprinting polymer.
[0043] The selective adsorption capacity of thiophene molecular imprinting polymer for thiophene was investigated by static adsorption test. A benzene solution containing 0.5% thiophene (mass fraction) was prepared, and then the thiophene molecular imprinting polymer was dispersed in the 0.5% thiophene benzene solution (the mass ratio of thiophene molecular imprinting polymer to benzene solution was 1:10), and adsorbed at 25°C for 3 hours. The adsorption performance of thiophene molecular imprinting polymer is shown in Table 1.
[0044] Table 1 Adsorption properties of thiophene molecular imprinting polymers
[0045] Thiophene removal rate (%) Thiophene adsorption capacity (mg / g) 66.2 33.1
[0046] Example 2
[0047] Step (1) and step (3) are the same as the preparation process of step (1) and step (3) of Example 1. Step (2) Surface silanization of mesoporous carbon-coated nano-iron tetroxide matrix: weigh 0.8g of mesoporous carbon-coated nano-iron tetroxide, then add 16mL of deionized water, 48mL of ethanol and 4mL of KH570, and ultrasonically disperse for 30min. After ultrasonication, under nitrogen protection, magnetic stirring, react in a 65°C water bath for 4h. After the reaction is completed, wait for the solution to cool, separate the product with a magnet, and then fully wash it with ethanol. The washed product is dried in a 60°C oven to obtain silanized mesoporous carbon-coated nano-iron tetroxide.
[0048] The adsorption performance of the thiophene molecular imprinting polymer obtained by static adsorption test according to the method of Example 1 is shown in Table 2.
[0049] Table 2 Adsorption properties of thiophene molecular imprinting polymers
[0050] Thiophene removal rate (%) Thiophene adsorption capacity (mg / g) 87.1 43.6
[0051] Example 3
[0052] Step (1) and step (2) are the same as the preparation process of step (1) and step (2) of Example 2. Step (3) Preparation of thiophene imprinted polymer: weigh 0.5g of silanized mesoporous carbon-coated nano-iron tetroxide and disperse it in 100mL of acetonitrile, ultrasonicate for 10min to make it evenly dispersed, then add 5mmol of thiophene and 20mmol of methacrylic acid, continue ultrasonication for 20min and magnetically stir at room temperature for 1 hour. Then add 20mmol of ethylene glycol dimethacrylate and 0.1g of azobisisobutyronitrile, magnetically stir, heat to 60°C under nitrogen protection, and react for 24h. After the reaction is completed, separate the product with a magnet, wash it three times with ethanol, and then repeatedly elute it with a mixed solution of methanol and acetic acid in a volume ratio of 9:1 until the presence of sulfur content is no longer detected in the eluent. Finally, the obtained product is dried in an oven at 60°C to obtain a thiophene molecular imprinted polymer.
[0053] The adsorption performance of the thiophene molecular imprinting polymer obtained by static adsorption test according to the method of Example 1 is shown in Table 3.
[0054] Table 3 Adsorption properties of thiophene molecular imprinting polymers
[0055] Thiophene removal rate (%) Thiophene adsorption capacity (mg / g) 81.4 40.7
[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a molecularly imprinted polymer, characterized in that: The following steps are involved: S1) mixing iron salt with asphalt, and calcining in a protective atmosphere to obtain mesoporous carbon-coated nano-iron tetroxide; S2) subjecting the mesoporous carbon-coated ferrosoferric oxide to silanization treatment to obtain silanized mesoporous carbon-coated ferrosoferric oxide; S3) mixing the silanized mesoporous carbon-coated ferrosoferric oxide, thiophene and functional monomers in an organic solvent, then adding a crosslinking agent and an initiator and heating in a protective atmosphere for reaction to obtain a molecular imprinting polymer.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the iron salt to the asphalt is (1-3):
1.
3. The preparation method according to claim 1, characterized in that: In the step S1), the calcination temperature is 500° C. to 600° C.; the calcination heating rate is 5 to 15° C. / min; and the calcination time is 0.5 to 3 hours.
4. The preparation method according to claim 1, characterized in that: The step S2) is specifically as follows: The mesoporous carbon-coated ferrosoferric oxide and a silane coupling agent are mixed in an alcohol solution, and heated to react in a protective atmosphere to obtain silanized mesoporous carbon-coated ferrosoferric oxide.
5. The preparation method according to claim 4, characterized in that: The ratio of the mesoporous carbon-coated ferrosoferric oxide to the silane coupling agent is (0.5-1) g: (2.5-5) mL.
6. The preparation method according to claim 4, characterized in that: The alcohol solution is a mixed solution of an alcohol solvent and water; the volume ratio of the alcohol solvent to water is (3-6): (1-2); The ratio of the mesoporous carbon-coated ferroferric oxide to the alcohol solution is (0.5-1) g: (40-80) mL; The mixing time is 10 to 60 minutes; the heating reaction temperature is 60° C. to 70° C.; and the heating reaction time is 3 to 5 hours.
7. The preparation method according to claim 1, characterized in that: The ratio of the silanized mesoporous carbon-coated ferrosoferric oxide, thiophene and functional monomer is 0.5 g: (2-5) mmol: (8-20) mmol; The ratio of the silanized mesoporous carbon-coated ferrosoferric oxide, the crosslinking agent and the initiator is 0.5 g: (8-20) mmol: (0.04-0.1) g.
8. The preparation method according to claim 1, characterized in that: The mixing time in step S3) is 10 to 100 minutes; The reaction temperature is 50°C to 70°C; the reaction time is 15 to 30 hours.
9. Molecularly imprinted polymer prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the molecularly imprinted polymer prepared by the preparation method according to any one of claims 1 to 8 in extracting thiophene from coking crude benzene.
Citation Information
Patent Citations
Benzothiophenes molecular imprinting polymeric adsorbent, preparing method and applications thereof
CN101229507B
Preparation method of magnetic material for removing dibenzothiophene from oil
CN102675537B
Molecular imprinting material for desulfurization and preparation method thereof
CN102731719A
Preparation method of carbon surface molecular imprinting two-dimensional composite film
CN109589808A
Molecularly imprinted polymer for removing thiophene sulfur in gasoline and preparation method of molecularly imprinted polymer
CN112794963A